2017
DOI: 10.5897/ajps2017.1519
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobium inoculation and sulphur fertilizer improved yield, nutrients uptake and protein quality of soybean (Glysine max L.) varieties on Nitisols of Assosa area, Western Ethiopia

Abstract: , respectively. The results clearly suggested that balanced application of S along with Rhizobium strain can affect grain and straw yield and nutrients uptake of soybean varieties, enhance their growth and improve grain quality protein as well as benefit on soil N balance in Sdeficient soils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
3
6
0
1
Order By: Relevance
“…Rhizobial inoculation and combined treatment of rhizobia inoculant and cattle manure enhanced N uptake more than the mineral fertilizer or cattle manure alone. This is in line with the reports of other researchers who found significant increment in uptake of major nutrients when inoculants were used in combination with cattle manure or other organic manure than inoculants or mineral fertilizer alone [17,23,16]. Another reason could be the high-quality organic manure that was used during the field experiment (Table 1).…”
Section: Nitrogen Fixation For Soybean At Sudan and Guinea Savannahssupporting
confidence: 91%
See 3 more Smart Citations
“…Rhizobial inoculation and combined treatment of rhizobia inoculant and cattle manure enhanced N uptake more than the mineral fertilizer or cattle manure alone. This is in line with the reports of other researchers who found significant increment in uptake of major nutrients when inoculants were used in combination with cattle manure or other organic manure than inoculants or mineral fertilizer alone [17,23,16]. Another reason could be the high-quality organic manure that was used during the field experiment (Table 1).…”
Section: Nitrogen Fixation For Soybean At Sudan and Guinea Savannahssupporting
confidence: 91%
“…A study conducted in Southern Spain also confirmed that addition of N fertilizer to inoculated soybean plants (50 kg N ha -1 ) did not increase seed yield in comparison with treatments that were only inoculated with Bradyrhizobia [25]. Other workers in Ethiopia also found that mineral nitrogen suppressed biological nitrogen in faba beans [23]. On the contrary, a study conducted in India on the effect of inoculation on soybean reported that application of starter nitrogen (20 kg N ha- 1 ) enhanced nodulation and yield of soybean [27].…”
Section: Nitrogen Fixation For Soybean At Sudan and Guinea Savannahsmentioning
confidence: 75%
See 2 more Smart Citations
“…Zn is involved in auxin metabolism like, tryptophane synthesis, tryptamine metabolism, protein synthesis, formation of nucleic acid and helps in utilization of nitrogen as well as phosphorus by plants (Ram and Katiyar, 2013). Similar to the current findings N uptake increase due to rhizobium inoculation, S and Zn application have been reported by several literatures (Abdalla et al, 2011;Das et al, 2016;Desta et al, 2015;El-kade and Mona, 2013;Hussain et al, 2011;Islam et al, 2013;Jay et al, 2012;Kesare, 2014;Mondal et al, 2005;Najar et al, 2011;Rokhzadi and Toashih, 2011;Shamima and Farid, 2006;Srinivasulu et al, 2015;Srivastava et al, 2006;Togay et al, 2008;Zaidi et al, 2003;Zerihun et al, 2017) Total phosphorus uptake…”
Section: Total Nitrogen Uptakesupporting
confidence: 82%